2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5625998
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cell (RGC) responses to different voltage stimulation parameters in rd1 mouse retina

Abstract: Retinal prostheses are being developed to restore vision for the blind with retinal diseases such as retinitis pigmentosa (RP) or age-related macular degeneration (AMD). Since neural prostheses depend upon electrical stimulation to control neural activity, optimal stimulation parameters for successful encoding of visual information are one of the most important requirements to enable visual perception. Therefore, in this paper, we focused on RGC responses to different stimulation parameters in degenerated reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Several studies have found that outer retinal degeneration can increase RGC activation thresholds to electrical stimulation; however, the majority of these studies examined indirect activation (Jensen and Rizzo, 2008, 2009, 2011; Ye et al, 2010; Goo et al, 2011; Jensen, 2012), or activation that could not be definitively classified as direct or indirect (Rizzo et al, 2003; Suzuki et al, 2004; O’Hearn et al, 2006; Ye et al, 2008). The studies examining direct RGC response thresholds have had inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that outer retinal degeneration can increase RGC activation thresholds to electrical stimulation; however, the majority of these studies examined indirect activation (Jensen and Rizzo, 2008, 2009, 2011; Ye et al, 2010; Goo et al, 2011; Jensen, 2012), or activation that could not be definitively classified as direct or indirect (Rizzo et al, 2003; Suzuki et al, 2004; O’Hearn et al, 2006; Ye et al, 2008). The studies examining direct RGC response thresholds have had inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, high contrast full-field visual stimuli from a computer monitor failed to evoke significant responses (Figure 4f-g). In contrast, full-field excitation using a 530 nm LED light elicited responses across the ECoG grid (Figure 4b-e), with a median of 16 channels (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) interquartile range) displaying significant responses (Figure 4b). This wide-spread activation of 8 3d), and likely reflects activation of opsin-expressing RGCs distributed widely in the retina.…”
Section: In Vivo Validation Of Optogenetic Viral Vectormentioning
confidence: 99%
“…For photopic vision assessment, animals were sedated in the operating room after a minimum of 10 minutes light adaptation and tested with a standard flash (0dB) to access combined rods and cones, and a flicker flash (0dB, 28Hz) to isolate cone response, with a background light intensity of 25 cds/m 2 . For examination of scotopic vision which isolates rod vision, animals were sedated in the housing room in the last 30 minutes of their normal dark cycle (12 and two types of light intensity were used; a small light intensity (-20bB), followed by a standard flash (0dB) measuring both maximal and oscillatory potentials.…”
Section: Visual Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these conditions result in the gradual deterioration of photoreceptor cells in the outer retina, including rods and cones, they do not impact the inner retinal ganglion nerve cells that constitute the optic nerve (Bhatnagar et al, 2019). The retinal prosthesis uses eyeglasses to transmit image data to an implant connected to the retina, which activates microsensors and converts electrical impulses into neurological signals, partially restoring vision in degenerative diseases (Ye et al, 2010;Chaudhari et al, 2016). Scientists are developing a nanoscale artificial retina, the bio-retina project, which uses specialized activation eyeglasses to transform natural light into electrical signals for image relay (Sarkar et al, 2023) (Figure 4).…”
Section: Journal Of Disability Research 2024mentioning
confidence: 99%